2011 Fifth International Conference on Secure Software Integration and Reliability Improvement 2011
DOI: 10.1109/ssiri.2011.26
|View full text |Cite
|
Sign up to set email alerts
|

Trust Observations in Validation Exercises

Abstract: This paper is concerned with an operational account of trust. It reports our experience in observing different trust aspects during a validation session for the assessment of a new tool and relevant operational concepts in the Air Traffic Management (ATM) domain. Despite the fact that trust is yet an elusive concept, our results show how monitoring trust can support the validation of alternative system settings and their operational aspects. This paper reports our experimental work on observing trust during va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
2
2
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…(d) Level of Automation: Another factor that may affect trust in the system is its level of automation (i.e., the degree to which the system acts on its own). Since higher levels of automation are more complex, thus potentially more opaque to the operator, higher levels of automation are frequently (Calhoun et al, 2009;Amato et al, 2011;Nam et al, 2019;Kira & Potter, 2009) found to engender less trust. To overcome this deficit transparency becomes more important when the system is more autonomous.…”
Section: Factors Affecting Trust In Automationmentioning
confidence: 99%
“…(d) Level of Automation: Another factor that may affect trust in the system is its level of automation (i.e., the degree to which the system acts on its own). Since higher levels of automation are more complex, thus potentially more opaque to the operator, higher levels of automation are frequently (Calhoun et al, 2009;Amato et al, 2011;Nam et al, 2019;Kira & Potter, 2009) found to engender less trust. To overcome this deficit transparency becomes more important when the system is more autonomous.…”
Section: Factors Affecting Trust In Automationmentioning
confidence: 99%
“…[16] found ratings of trust higher in a condition prioritizing a list of possible engagements than in either an unprioritized list or higher levels of automation. [27] similarly found a lower level of automation preferred for aiding an air traffic control (ATC) task. [26] report higher ratings of trust for management by consent (lower LOA) than for management by exception (higher LOA) as well.…”
Section: B Degree Of Automationmentioning
confidence: 99%